The myth of American idealism : how U.S. foreign policy endangers the world - Chomsky, Noam; Robinson, Nathan J. (Penguin Press, 2024)
"The Myth of American Idealism offers a timely and comprehensive introduction to the incisive critiques of U.S. power that have made Noam Chomsky a "global phenomenon," one of the most widely known public intellectuals of all time. Surveying the history of U.S. military and economic activity around the world, Chomsky and his co-author Nathan J. Robinson vividly trace the way the American pursuit of global domination has wrought havoc in country after country - without, ironically, making Americans any safer. And they explore how dominant elites in the United States have pushed self-serving myths about this country's commitment to "spreading democracy," while pursuing a reckless foreign policy that served the interest of few and endangered all too many. Chomsky and Robinson range across the globe, offering penetrating accounts of Washington's relationship with the Global South, its role in the Israeli-Palestinian conflict, and the wars in Iraq and Afghanistan -all justified with noble stories about humanitarian missions and the benevolent intentions of American policy makers. The same kinds of myths that have led to repeated disastrous wars, they argue, are now driving us closer to wars with Russia and China that imperil humanity's future. Examining nuclear proliferation and climate change, they show how U.S. policies are continuing to exacerbate global threats. For well over half a century, Noam Chomsky has committed himself to exposing governing ideologies and criticizing his country's unchecked use of military power. At once thorough and devastating, urgent and provocative, The Myth of American Idealism offers a highly readable entry to the conclusions he has come to after a lifetime of thought and activism"--